Characteristics of the litter dynamics in a Moso bamboo forest after strip clearcutting - Zheng, Yaxiong; Fan, Shaohui; Guan, Fengying; Zhang, Xuan; Zhou, Xiao (Frontiers in Plant Science, 2022)
Introduction The quality of new Moso bamboo trees has been found to decrease in the years following strip cutting (SC) events. It is thus essential that we improve our knowledge of nutrient return after strip cutting in Moso bamboo forests to help facilitate sustainable management. Methods In this investigation the dynamics of nutrient return were monitored in plots with 8 m wide strip cutting (SC), their reserve belts (RB), and a traditionally managed forest (CK) as the control, for 5 years after cutting. Results The results showed that strip cutting significantly reduced nutrient return (p< 0.05), but as the plots recovered, the nutrient levels also recovered to match those of the control. The high densities in the RB no longer increase nutrient return. Five years after SC there was no significant difference in nitrogen and phosphorus returns among the three treatment plots, but potassium returns in the SC plot were significantly higher than those in the RB (p< 0.05). From 2–5 years after cutting, the litter decomposition rate in the RB was significantly higher than in the SC and CK (p< 0.05). In addition, the decomposition rate in the SC plot was significantly accelerated five years after logging, which suggests that long-term strip cutting management may lead to the restriction of nutrients on the growth and development of new trees. Discussion The results indicate that nutrients should be added via artificial fertilization in the future.